Pengaruh Penambahan Titanium Dioksida Terhadap Kekasaran Permukaan dan Stabilitas Warna Pada Basis Gigi Tiruan Resin Akrilik Polimerisasi Panas - Angelia, Revina (International Journal Labs, 2025)
Heat-polymerized acrylic resin (RAPP) is the most commonly used denture base material but has deficiencies in physical and mechanical properties. Titanium dioxide as a nanotechnology reinforcing material can improve material properties but its effects on surface roughness and color stability need evaluation. To determine the effect of titanium dioxide addition at concentrations of 0.5%, 1%, and 1.5% on surface roughness and color stability of RAPP denture base. Experimental laboratory research with post only control group design. Samples were divided into 4 groups: control without titanium dioxide, and treatment groups with titanium dioxide addition of 0.5%, 1%, and 1.5% (n=6 each group). Surface roughness was measured using surface roughness tester and color stability using portable colorimeter. Data were analyzed using independent T-test (p?0.05). Mean surface roughness values decreased significantly from 0.192±0.004 µm (control) to 0.187±0.001 µm (0.5%), 0.156±0.006 µm (1%), and 0.119±0.002 µm (1.5%) with p<0.05. Color stability values increased significantly from 0±0 ?E (control) to 27.71±0.25 ?E (0.5%), 30.98±0.30 ?E (1%), and 35.41±0.11 ?E (1.5%) with p<0.05. Titanium dioxide addition significantly reduces surface roughness within clinically acceptable limits but increases color changes beyond clinical limits (?E>3.7).